THE EFFECT OF MOTIVATION, COMMUNICATION AND FINANCIAL COMPENSATION ON EMPLOYEE PERFORMANCE AT ADIS DIMENSION FOOTWEAR COOPERATIVE COMPANY BALARAJA TANGERANG - Muhammad Farhan Maulana; Wawan Prahiawan; Vera Maria (Sekolah Tinggi Pariwisata Mataram, 2022)
This study aims to determine the effect of motivation, communication and non-financial compensation on employee performance at the Cooperative Adis Dimension Footwear Company Balaraja Tangerang. The type of research used is quantitative with a descriptive approach, the population in this study are employees of the Cooperative Adis Company Tangerang, totaling 43 people. The sample of this study amounted to 43 respondents who were determined by the saturated sample formula. Testing of research instruments was carried out on employees of the Cooperative of Adis Company Tangerang, with random sampling, and in measuring the questionnaire using a measurement scale of 1-10, the data analysis methods used were data quality tests, classical assumption tests and multiple linear tests with the help of SmartPLS software. version 3.0. The results of this study on the first hypothesis obtained tcount 2.112 > ttable 1.98 with a significance level <0.05, meaning that there is a positive and significant influence of motivation on employee performance at the Cooperative Adis Dimension Footwear Company Balaraja. These results support the proposed hypothesis (accepted). The second hypothesis was obtained that tcount was 2.520 > ttable 1.98 with a significance level of <0.05, meaning that there was a significant positive and significant effect of communication on employee performance at the Cooperative Adis Dimension Footwear Company Balaraja. These results support the proposed hypothesis (accepted). The third hypothesis is obtained tcount 2,324 > ttable 1.98 with a significance level > 0.05, meaning that there is a positive and significant effect of non-financial compensation on employee performance at the Cooperative Adis Dimension Footwear Company Balaraja. These results support the proposed hypothesis (accepted).